Renal Transplantation in Secondary Amyloidosis Associated with Tuberculosis - Vivek B. Kute; Aruna V. Vanikar; Himanshu V. Patel; Manoj R. Gumber; Pankaj R. Shah; Pranjal R. Modi; Hargovind L. Trivedi (Case Reports in Transplantation)
Although end-stage renal disease (ESRD) related to AA amyloidosis nephropathy secondary to tuberculosis is most common in our country, there are limited data concerning patient and graft outcome after renal transplantation (RTx). To the best of our knowledge, this is the first report of RTx in ESRD patient with secondary amyloidosis due to tuberculosis from India. A 30-year-old female with past history of pulmonary tuberculosis 3 years back was admitted with complaint of gradually progressive pedal oedema and nausea for 3 months. Renal biopsy was suggestive of secondary renal amyloidosis with vascular involvement and chronic tubulointerstitial involvement. She was transplanted with kidney from her 28-year-old brother with 3/6 human leukocyte antigen match. She had immediate good graft function without any perioperative complications (cardiovascular, infections, rejection and delayed graft function). She was discharged with serum creatinine of 0.8 mg/dL. Her last serum creatinine level was 0.9 mg/dL with cyclosporine level of 100 mg/dL at 9-month followup without any medical or surgical complication. The quality of life also improved after transplantation. With careful selection, ESRD patients with secondary amyloidosis due to tuberculosis are eligible for RTx with favorable outcome and improved quality of life.